CEREBRAL ISCHEMIC STROKE: SEQUELS OF CASCADE - ASHU AGGARWAL; PARVEEN AGGARWAL; MAMTA KHATAK; SUNIL KHATAK (International Journal of Pharma and Bio Sciences, 2010)
Cerebral Ischemia (stroke) is one of the foremost causes of high morbidity and mortality for both developed and developing countries. Cerebral ischemia impairs the normal neurological functions which are triggered by a complex series of biochemical and molecular mechanism. Understanding of mechanisms of injury and neuroprotection in this disease is important to learn new target sites to treat ischemia. In this article, there is clear understanding of ischemic cascade followed by the mechanism of all damaging factors like energy failure, excitotoxicity, oxidative stress, neuroinflammation, cell death modes: necrosis, apoptosis along with histological changes. Further it also discloses the different epidemiology based on the age, gender and races along with current status of the prevalence in India in comparison with western world. The present authors also describe and relate aponecrosis and necroptosis with cerebral ischemia. The main emphasis is given and described along with diagrammatic view.